2021
DOI: 10.1177/0194599820984780
|View full text |Cite
|
Sign up to set email alerts
|

Tracheotomy in COVID‐19 Patients: A Systematic Review and Meta‐analysis of Weaning, Decannulation, and Survival

Abstract: Objectives A systematic review and meta-analysis was conducted to determine the cumulative incidences of decannulation and mechanical ventilation weaning in patients with coronavirus disease 2019 (COVID-19) who have undergone a tracheotomy. Weighted average mean times to tracheotomy, to decannulation, and to death were calculated from reported or approximated means. Data Sources PubMed, SCOPUS, CINAHL, and the Cochrane library. Review Methods Studies were screened by 3 investigators independently. Preferred Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
52
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 54 publications
7
52
0
2
Order By: Relevance
“…Moreover, overall weighted means reported in this study are estimates, borne from differences in reporting between individual studies. As highlighted by Benito et al, this likely gives rise to selection bias 69 . Notwithstanding, the current study provides the largest meta-analysis on tracheostomy outcomes in COVID-19 patients to date, and includes an overview of key tracheostomy outcomes, as well as comparisons between clinically relevant patient cohorts.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, overall weighted means reported in this study are estimates, borne from differences in reporting between individual studies. As highlighted by Benito et al, this likely gives rise to selection bias 69 . Notwithstanding, the current study provides the largest meta-analysis on tracheostomy outcomes in COVID-19 patients to date, and includes an overview of key tracheostomy outcomes, as well as comparisons between clinically relevant patient cohorts.…”
Section: Discussionmentioning
confidence: 97%
“…A previous meta-analysis on tracheostomy outcomes in COVID-19 patients by Benito et al identified the cumulative incidence of mortality, mechanical weaning and decannulation across 18 studies 69 . Although this study provided useful insight into overall mortality, weaning and J o u r n a l P r e -p r o o f decannulation in the COVID-19 patient population, estimates given were limited by the comparatively short follow up durations reported at the time of meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, each of these methods has considerable limitations. [1][2][3] Unfortunately, the authors did not present any differences in the results depending on the tracheostomy method used.…”
Section: Shared Decision-making and Stakeholder Engagement In Covid-19 Tracheostomymentioning
confidence: 88%
“…Understanding what patients and families want can inform choice or timing of interventions beyond simply surviving. 3 Early tracheostomy may mitigate airway injury risks, 4 allow earlier restoration of speech and swallowing, and avoid prolonged sedation, which risks muscle wasting, cognitive impairment, and psychiatric morbidity.…”
Section: Shared Decision-making and Stakeholder Engagement In Covid-19 Tracheostomymentioning
confidence: 99%
See 1 more Smart Citation